Sex Differences in Medicine Acceptability: A New Factor to Be Considered in Medicine Formulation - Fabrice Ruiz; Alexander Keeley; Patrick Léglise; Catherine Tuleu; Célia Lachuer; Jean-Paul Rwabihama; Nathalie Bachalat; Imad Boulaich; Fattima Abdallah; Maité Rabus; Annie-Claude Ribemont; Hugues Michelon; et al. (MDPI AG, 2019)
Palatability is a recognized driver of medicine acceptability in pediatrics but deemed less relevant in older populations due to sensory decline. Preliminary findings from an observational study implicated palatability problems with one Alzheimer’s medicine. Among 1517 observer reports combining multiple measures on medicines uses in patients aged over 64, we focused on two original formulations of memantine (Ebixa®, tablets (n = 25) and oral solution (n = 60)). Evaluations were scored with an acceptability reference framework (CAST), the rodent Brief Access Taste Aversion (BATA) model tested aversiveness. Focusing on women treated with Ebixa® (n = 54), the oral formulation sub-group was classified as “negatively accepted”, while the coated tablet was associated with the “positively accepted” cluster. In men, both formulations belonged to the “positively accepted” profile. Using BATA, the original oral solution was categorized as highly aversive/untolerated while solutions of excipients only were well tolerated. Furthermore, the number of licks was significantly lower in female than in male rats. These results revealed that medicine palatability remains important for acceptability in older populations. Moreover, converging results from humans and animal models highlighted that palatability profiles can significantly vary between the sexes. These drivers should be closely considered during drug development to enhance acceptability in this population.